Effect of GaN surface treatment on Al2O3/n-GaN MOS capacitors - Hossain, T.; Wei, Daming; Edgar, James H.; Garces, N. Y.; Nepal, N.; Hite, J. K.; Mastro, M. A.; Eddy C.R, Jr.; Meyer H.M, III (My University, 2015)
The surface preparation for depositing Al2O3 for fabricating Au/Ni/Al2O3/n-GaN (0001) metal oxide semiconductor (MOS) capacitors was optimized as a step toward realization of high performance GaN MOSFETs. The GaN surface treatments studied included cleaning with piranha (H2O2:H2SO4 = 1:5), (NH4)2S, and 30% HF etches. By several metrics, the MOS capacitor with the piranha-etched GaN had the best characteristics. It had the lowest capacitance–voltage hysteresis, the smoothest Al2O3 surface as determined by atomic force microscopy (0.2 nm surface roughness), the lowest carbon concentration (∼0.78%) at the Al2O3/n-GaN interface (from x-ray photoelectron spectroscopy), and the lowest oxide-trap charge (QT = 1.6 × 1011 cm−2eV−1). Its interface trap density (Dit = 3.7 × 1012 cm−2eV−1), as measured with photon-assisted capacitance– voltage method, was the lowest from conduction band-edge to midgap.
Citation: Hossain, T., Wei, D., Edgar, J. H., Garces, N. Y., Nepal, N., Hite, J. K., . . . Meyer H.M, III. (2015). Effect of GaN surface treatment on Al2O3/n-GaN MOS capacitors. Journal of Vacuum Science and Technology B: Nanotechnology and Microelectronics, 33(6). doi:10.1116/1.4931793
Keywords: Aluminum; Atomic Force Microscopy; Capacitance; Capacitors; Carbon; Dielectric Devices